Adaptive Wavelet Schwarz Methods for the Navier-Stokes Equation. (2nd October 2016) - Dahlke, Stephan; Lellek, Dominik; Lui, Shiu Hong; Stevenson, Rob
ABSTRACT: In this article, we are concerned with domain decomposition methods for the stationary incompressible Navier-Stokes equation. We construct an adaptive additive Schwarz method based on discretization by means of a divergence-free wavelet frame. We prove that the method is convergent and asymptotically optimal with respect to the degrees of freedom involved.